Management of property rates in Tenaga Nasional Berhad (TNB) / Man Yusop - Yusop, Man (2000)
This dissertation is about the management of property rates in Tenaga Nasional Berhad. This topic is not a popular topic in any research or study. Not much was written by any writers about rates in Malaysia. Because of this, the level of understanding by Malaysian about property rates is very low even though most of the households in urban areas pay rates. Very few books or articles about property rates in Malaysia are available. Hence, the writer encountered some problem in writing this Dissertation because of insufficient materials or information. Getting figures or data from Tenaga Nasional Berhad is not an easy task because most of the figures or data are still kept in old files with some dated from the 70s. The database used is not an integrated system so, extracting, analysing or manipulating the data is difficult. Two important organisations are involved in this study of property rates namely: i) Tenaga Nasional Berhad including its subsidiaries which is the rates payee, and ii) Local Authority, which charge rates.